Malaysian halal certification and Malaysia as global halal hub: the awareness and acceptance by the OIC members food manufacturers - Abdul Rahman, Rozailin; Mohamed, Zainal Abidin; Rezai, Golnaz (2015)
Malaysia as a member of the Organization of Islamic Conference (OIC) is pushing its Halal certification as an international standardized logo to be used by all Muslim nations. This move is supported by the OIC members, but other countries such as Turkey, Pakistan, and Abu Dhabi are also starting to show interest in promoting their own Halal logo. Questionnaires were distributed to 100 OIC’s Halal food manufacturers during the 9th International Halal Showcase 2012, while 200 respondents were contacted through online survey. The results suggested that Malaysia in terms of strategic location, expertise in Halal research, and it background in Halal are the direct measures of the food manufacturers’ attitudes to accept Malaysian Halal Certification and Malaysia as the Halal Hub among themselves. Furthermore, the influence of perceived behavioral control including the processing fees, information exposure, and government incentives make them more aware about trusted Halal certification.